Hubungan Lama Penggunaan KB Suntik 3 Bulan Dengan Kenaikan Berat Badan Akseptor KB di TPMB Ny. I Kota Pasuruan: Sari Fitri Aprilia, Lia Dharmayanti - Sari Fitri Aprilia; Lia Dharmayanti (Jurnal Persada Husada Indonesia, 2025)
The Family Planning (KB) Program is an effort to regulate child birth, birth spacing, and the ideal age of childbirth through promotion, protection, and assistance in accordance with reproductive rights to create a quality family, which can be done by using contraceptives such as 3-month injectable contraceptives. 3-month injectable contraceptives, which contain the synthetic hormone Depo Medroksy Progesterone Acetate (DMPA), often cause side effects in the form of weight gain due to the influence of the hormone progesterone on the metabolism of carbohydrates into fat, increased appetite, and decreased physical activity. This study aims to determine the relationship between the duration of use of 3-month injectable contraceptives and weight gain in KB acceptors at TPMB Ny.I, Pasuruan City, and to describe the distribution of frequency of use and weight gain status. The research method uses an analytical survey design with a cross-sectional approach on 20 3-month injectable contraceptive acceptors who visited in December 2024, with data collection through checklists and weight measurements, analyzed using the chi-square test (Î± = 0.05). The results showed that 70% of respondents used 3-month injectable contraception for more than 1 year and 90% experienced weight gain, with a p value = 0.02 < 0.05 indicating a significant relationship (Ha accepted, H0 rejected); all respondents with use > 1 year (100%) experienced weight gain. The conclusion of the study stated that there was a significant relationship between the length of use of 3-month injectable contraception and weight gain, so it is recommended to increase counseling (KIE) on weight management through diet and exercise, and these results can be a reference for further research in the field of reproductive health.